Unambiguously defined and recognized seabed protection targets are necessary for successful implementation of MPAs. (June 2022) - Vrooman, Jip; van Sluis, Christiaan; van Hest, Floris; Lindeboom, Han; Murk, Albertinka
Abstract: Bottom-impacting fisheries affect benthic marine ecosystems through extraction of resources and physical habitat impact. To protect natural values against human impacts, marine protected areas (MPAs) are being implemented. In practice, however, these do not necessarily provide full protection against bottom-impacting fisheries. Sometimes only certain types of fishing are prohibited, or only during certain periods of the year. In the Netherlands currently 20% of the North Sea is declared MPA. Most areas include ambiguously defined conservation goals for the seafloor, such as protection against 'note-worthy' impact. The government, fishermen and NGOs state that respectively 4%, 20% and less than 1% of the Dutch North Sea floor is currently protected against bottom-impacting fisheries. These diverging perspectives hamper successful communication, and result in different views on whether the Netherlands meets (inter)national targets. This paper reveals the fact-base and rationale behind these different perspectives, and illustrates these in more detail for three areas in the Dutch North Sea. We suggest five steps to help avoid miscommunication, operationally define Dutch MPAs and ensure their effectiveness; (1) explicitly specify protection goals beforehand, (2) substantiate why and how the protection goals under (1) will be reached with the proposed measures, (3) define measurable targets, (4) ensure enforcement and (5) monitor closely and adapt when needed. The explicit fact-base presented in this paper aims to contribute to a constructive discussion about protection goals and necessary measures, and prevents Babylonian confusion. Recent new developments concerning the 'North Sea Agreement', as well as the EU Biodiversity Strategy for 2030, have the potential to solve several of the abovementioned challenges. Highlights: MPA's do not necessarily provide full protection against bottom-impacting fisheries. Stakeholders can have strongly diverging perspectives on protection status. These hamper communication, negotiation and effective seafloor protection. Five steps are proposed to avoid miscommunication and improve MPA effectiveness.